Relationship between Knowledge Level and Hand Hygiene Compliance among Nurses at Kudungga Sangatta Regional Hospital - Muhammad Suhaimi; Edi Sukamto; Ratanto (Formosa Journal of Applied Sciences, 2024)
Hand hygiene is an effective step to break the chain of infection transmission. Root cause analysis shows that the knowledge factor is a determinant of hand hygiene compliance behavior. Knowledge of correct hand hygiene can provide protection against cross-contamination of diseases from one patient to another. The aim is to determine the relationship between knowledge level and hand hygiene compliance among nurses at Kudungga Regional Hospital. This type of quantitative research uses cross-sectional methods. The population in this study was 185 nurses at Kudungga Regional Hospital. Sample of 185 people/ The test results obtained a p-value = 0.000 (<0.05) with an odds ratio = 8.509. There is a relationship between the level of knowledge and hand hygiene compliance among nurses at Kudungga Sangatta Regional Hospital. It is hoped that the hospital will be able to improve the quality of service health to pay more attention to the risk of infection in the work environment.